2014
DOI: 10.2337/db13-1044
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Signals Through the Dorsal Vagal Complex to Regulate Energy Balance

Abstract: Insulin signaling in the hypothalamus regulates food intake and hepatic glucose production in rodents. Although it is known that insulin also activates insulin receptor in the dorsal vagal complex (DVC) to lower glucose production through an extracellular signal-related kinase 1/2 (Erk1/2)-dependent and phosphatidylinositol 3-kinase (PI3K)-independent pathway, it is unknown whether DVC insulin action regulates food intake. We report here that a single acute infusion of insulin into the DVC decreased food intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 34 publications
(57 reference statements)
1
32
1
Order By: Relevance
“…The dorsal vagal complex (DVC), located in the brainstem, is another key brain site known to regulate several autonomic functions, including peripheral glucose and energy homeostasis, via neural and hormonal signals [21]. Indeed, studies have confirmed that insulin [22,23], glucagon-like peptide 1 (GLP-1) [24,25] and leptin [26] signalling in the DVC regulate glycaemia and/or feeding behaviour. In light of the fact that glucagon receptors are also abundantly expressed in the brainstem [1,27], and peripherally administered glucagon alters neuronal activity in the brainstem [28], it was plausible that, analogous to the MBH, glucagon could initiate a signalling cascade in the DVC to regulate peripheral metabolism.…”
Section: Dorsal Vagal Complex Glucagon Action In Glucose Controlmentioning
confidence: 99%
“…The dorsal vagal complex (DVC), located in the brainstem, is another key brain site known to regulate several autonomic functions, including peripheral glucose and energy homeostasis, via neural and hormonal signals [21]. Indeed, studies have confirmed that insulin [22,23], glucagon-like peptide 1 (GLP-1) [24,25] and leptin [26] signalling in the DVC regulate glycaemia and/or feeding behaviour. In light of the fact that glucagon receptors are also abundantly expressed in the brainstem [1,27], and peripherally administered glucagon alters neuronal activity in the brainstem [28], it was plausible that, analogous to the MBH, glucagon could initiate a signalling cascade in the DVC to regulate peripheral metabolism.…”
Section: Dorsal Vagal Complex Glucagon Action In Glucose Controlmentioning
confidence: 99%
“…Indeed, direct administration of insulin into the DVC lowers food intake as early as 90 min compared with DVC saline infusions (Filippi et al . ). The mechanism underlying DVC insulin‐induced satiety involves the activation of DVC Erk1/2, because molecular and chemical inhibition of Erk1/2 signalling negates the ability of DVC insulin infusion to reduce feed et al .ing.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, direct inhibition of DVC Erk1/2 per se induces obesity (Filippi et al . ), while DVC leucine sensing activates Erk1/2 to lower feeding (Blouet & Schwartz, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracerebroventricular (ICV) injection of insulin in the mediobasal hypothalamus (MBH) decreased hepatic glucose production (HGP) (Obici et al, 2002b;Pocai et al, 2005), while selective decrease in insulin receptor levels in the hypothalamus resulted in hyperphagia and increased fat mass (Obici et al, 2002a). In rodents, the dorsal vagal complex (DVC) of the brain is another important regulator of glucose metabolism (Filippi et al, 2012) and food intake (Filippi et al, 2014). In particular, the nucleus of the solitary tract (NTS) in the DVC senses insulin and triggers a neuronal relay to decrease HGP and food intake (Filippi et al, 2012;Filippi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%